Study of LaSiO3Cl:Ce3+,Tb3+ and Ca5B2SiO10:Eu3+ Phosphors for Improving Hue Standard and Illuminating Beam of WLEDs - Dieu An Nguyen Thi; Phan Xuan Le (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
Remote phosphor arrangements usually have low color quality and superior lumen output to that of conformal phosphor arrangements and in-cup phosphor arrangements. For this reason, many researches are done so that we could enhance the chromatic quality for the remote phosphor arrangements. For this research, we are suggesting the double-layer remote phosphor arrangement to boost the CRI (short for color rendering index) as well as the CQS (short for color quality scale) in WLED devices. Three identical WLED arrangements which have dissimilar chromatic temperature which covers 5600 K, 8500 K will be used in this paper. The initial idea involves placing one sheet of blue phosphor LaSiO3Cl:Ce3+,Tb3+ or one sheet of red phosphor Ca5B2SiO10:Eu3+ over a sheet of yellow phosphor YAG:Ce3+. After that, seek an appropriate concentration of Ca5B2SiO10:Eu3+ so that we could obtain the most desirable chromatic performance. Judging the result, the element Ca5B2SiO10:Eu3+ seem to help improve the CRI and CQS levels. Particularly, the greater the concentration of La2O3:Eu3+ is, the greater level the CRI and the CQS will get, because of the boost in red illumination within the WLED devices. In addition, the blue phosphor layer LaSiO3Cl:Ce3+,Tb3+ helps increase the lumen output. But the decline of the lumen as well as the chromatic performance manifests if the concentration of LaSiO3Cl:Ce3+,Tb3+ and Ca5B2SiO10:Eu3+ is beyond required level. This is demonstrated by utilizing the theory of Mie-scattering as well as the law of Beer–Lambert. This research’s result is important for the augmentation of white light performance in the WLED devices.